Prognosis of Intracerebral Hemorrhage Related to Antithrombotic Use: An Observational Study From the Swedish Stroke Register (Riksstroke). Issue 3 (10th February 2021) - Apostolaki-Hansson, Trine; Ullberg, Teresa; Pihlsgård, Mats; Norrving, Bo; Petersson, Jesper
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: To date, large studies comparing mortality and functional outcome of intracerebral hemorrhage (ICH) during oral anticoagulant (OAC), antiplatelet, and nonantithrombotic use are few and show discrepant results. Methods: We used data on 13 291 patients with ICH registered in Riksstroke between 2012 and 2016 to compare 90-day mortality and functional outcome following OAC-related ICH (n=2300), antiplatelet-related ICH (n=3637), and nonantithrombotic ICH (n=7354). Univariable and multivariable Cox regression analyses, with adjustment for relevant confounders, were used to compare 90-day mortality. Early (≤24 hours and 1–7 days) and late (8–90 days) mortality was also studied in subgroup analyses. Univariable and multivariable 90-day functional outcome, based on self-reported modified Rankin Scale, was determined using logistic regression. Results: Patients with antithrombotic treatment were more often prestroke dependent, older, and had a larger comorbidity burden compared with patients without antithrombotic treatment. At 90 days, antiplatelet and OAC were associated with an increased death rate in multivariable analysis (antiplatelet ICH: hazard ratio, 1.23 [95% CI, 1.14–1.33]; OAC ICH: hazard ratio, 1.40 [95% CI, 1.26–1.57]) compared with nonantithrombotic ICH (reference). OAC ICH and antiplatelet ICH were associated with higher risk of early mortality (≤24 hours: OAC ICH: hazard ratio, 1.93 [95% CI, 1.57–2.38]; antiplatelet ICH: hazard ratio, 1.32 [95% CI, 1.13–1.54]). In multivariable analysis, the odds ratios for the association of antiplatelet and OAC treatment on functional dependency (modified Rankin Scale score, 3–5) at 90 days were nonsignificant (antiplatelet: odds ratio, 1.07 [95% CI, 0.92–1.24]; OAC: odds ratio, 0.96 [95% CI, 0.76–1.22]). Conclusions: In this large observational study, we found that 90-day mortality outcome was worse not only in OAC ICH but also in antiplatelet ICH, compared with patients with nonantithrombotic ICH. Antiplatelet ICH is common and is a serious condition with poor clinical outcome. Further studies are, therefore, warranted in determining the appropriate clinical management of these patients.